Analysis of the Influence of Ease and Usefulness on Interest in Using QRIS in Micro, Small and Medium Enterprises (MSMEs) in Jempong Baru Village - Ismayadi (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This research aims tofor the Analysis of the Influence of Ease and Usefulness on Interest in Using QRIS in Micro, Small and Medium Enterprises (MSMEs) in Jempong Baru Village with the formulation of the problem to analyze the influence of ease on interest in using QRIS and analyze the influence of usefulness on interest in using QRIS which was carried out in Jempong Baru Village, Mataram City. Method - The types of research are:quantitative research type where quantitative research uses research based on postpositivism philosophy, used to research a particular population or sample. In this study, the sample taken used non-probability sampling technique. Non-probability sampling is a sampling technique that does not provide equal opportunities or chances for each member of the population to be selected as a sample. The sampling technique in this study used purposive sampling technique. Purposive sampling is a sampling technique with certain considerations. The number of samples was 30 MSMEs in Jempong Baru Village. The data obtained from the questionnaire was then processed using SPSS Version 16.0 software. Result - The results of this study indicate that the influence of the Ease Variable on the Interest Variable in using QRIS in Micro, Small and Medium Enterprises (MSMEs) in Jempong Baru Village, Mataram City is 83%. This means that the ease variable has a positive and significant influence on the Interest variable in using QRIS. This shows that the easier it is to use the QRIS service, the higher the interest in using the QRIS service. While the influence of the Benefit Variable on the Interest Variable in using QRIS in Micro, Small and Medium Enterprises (MSMEs) is 72% in Jempong Baru Village, Mataram City. This means that the benefit variable has a positive and significant influence on the Interest variable in using QRIS. This shows that the more benefits received and obtained by QRIS users, the higher the interest in using QRIS. Implication - This finding shows the important role of technology in supporting people's economic activities, especially in digital transaction activities. In addition, the role of technology increases efficiency, reduces costs, and creates new economic opportunities. This technology enables faster, safer, and more affordable transactions, as well as enabling wider access to markets and financial services. Originality - This analysis provides a more comprehensive explanation regardingEase and Benefits of Interest in Using QRISin Jempong Baru Village. This review contributes to the literature by identifying the convenience, benefits and weaknesses of QRIS in Jempong Baru Village.. Keywords:                     Convenience, Benefits, Interest, QRIS and MSMEs.